A novel pollution index to assess the metal bioavailability and ecological risks in sediments. (June 2023) - Chen, Chih-Feng; Lim, Yee Cheng; Ju, Yun-Ru; Albarico, Frank Paolo Jay B.; Chen, Chiu-Wen; Dong, Cheng-Di
Abstract: The chemical forms of metals in sediments of ports around Taiwan were investigated using sequential extraction. Based on the availability of different chemical forms, novel indices such as bioavailability, mobility, availability, and availability risk of metals in sediments were developed. The results showed that Co, Zn, Pb, Mn, and Cu were mainly present in available forms (49–84 %), and the proportion of oxidative or reductive fractionation was the highest. This suggests that the redox potential is a major factor for metal mobility in the sediments. The results from the proposed indexes showed that metals in sediments have low bioavailability but high to very high mobility and availability. Primarily, the proposed index is more appropriate, as the current index for assessing total metal content may overestimate the level of risk. The indexes established can comprehensively evaluate the bioavailability, mobility, availability, and ecological risk of metals in sediments. Graphical abstract: Unlabelled Image Highlights: Novel indices for heavy metal bioavailability and ecological risks are proposed. Chemical forms of heavy metal in port sediments around Taiwan are investigated. The bioavailability and availability of Mn and Cu in port sediments are high. Short oxygen events may increase sedimentary Mn bioavailability. Copper has high availability and ecological risk as a major pollutant.